2021
DOI: 10.1038/s41467-021-27295-4
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Rad26-assisted rescue of stalled RNA polymerase II in transcription-coupled repair

Abstract: Transcription-coupled repair is essential for the removal of DNA lesions from the transcribed genome. The pathway is initiated by CSB protein binding to stalled RNA polymerase II. Mutations impairing CSB function cause severe genetic disease. Yet, the ATP-dependent mechanism by which CSB powers RNA polymerase to bypass certain lesions while triggering excision of others is incompletely understood. Here we build structural models of RNA polymerase II bound to the yeast CSB ortholog Rad26 in nucleotide-free and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 67 publications
0
10
0
Order By: Relevance
“…We propose that the steric exclusion of Spt4/5 by the lesion-induced strong interaction between Rad26 and Rpb4/7 is a major step in committing a lesion-stalled Pol II to TC-NER. Furthermore, a previous computational study suggested that tethering Rad26-NTD with Pol II Rpb4/7 is important for Pol II-Rad26 complex assembly and plays a key role in anchoring Rad26 to Pol II and establishing a productive orientation with respect to the transcription bubble (30).…”
Section: Discussionmentioning
confidence: 99%
“…We propose that the steric exclusion of Spt4/5 by the lesion-induced strong interaction between Rad26 and Rpb4/7 is a major step in committing a lesion-stalled Pol II to TC-NER. Furthermore, a previous computational study suggested that tethering Rad26-NTD with Pol II Rpb4/7 is important for Pol II-Rad26 complex assembly and plays a key role in anchoring Rad26 to Pol II and establishing a productive orientation with respect to the transcription bubble (30).…”
Section: Discussionmentioning
confidence: 99%
“…69 Even though these statistical techniques have not been applied to other RNA-based machines involved in RNA metabolism, remarkable applications were done in related systems. [111][112][113][114][115] These methods therefore appear to be a powerful instrument in helping to elucidate the working principles of RNP-machineries.…”
Section: Unraveling the Molecular Principles Of Rnp-machinery Functionmentioning
confidence: 99%
“…Adding to the complexity, NER features two sub-pathways, global genome NER (GG-NER) and transcription-coupled NER (TC-NER), that differ only in the damage recognition step. TC-NER 4 6 is essential for lesion removal from the template strand during transcription and is activated by the recruitment of Cockayne Syndrome B protein (CSB) to lesion-arrested RNA polymerase II (Pol II) 7 12 . By contrast, in GG-NER a heterotrimeric complex of XPC, HR23B and Centrin 2 (CETN2) 13 detects the lesion and, in a twist-to-open mechanism, melts the DNA duplex at the damaged site 14 19 .…”
Section: Introductionmentioning
confidence: 99%